2018
DOI: 10.1186/s12960-017-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving local health through community health workers in Cambodia: challenges and solutions

Abstract: BackgroundVolunteer community health workers (CHWs) are an important link between the public health system and the community. The ‘Community Participation Policy for Health’ in Cambodia identifies CHWs as key to local health promotion and as a critical link between district health centres and the community. However, research on the challenges CHWs face and identifying what is required to optimise their performance is limited in the Cambodian context. This research explores the views of CHWs in rural Cambodia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Not different from previous studies [e.g., Maravilla et al (53)], non-pregnant adolescents in the current study were more likely to have access to pregnancy prevention information from health facilities and health workers compared to pregnant adolescents. Available literature has shown that health workers are effective in the provision of community health information to both young and old people on SRH issues to develop not only adolescent reproductive health but also a wider range of maternal and child health issues (67)(68)(69). Similarly, although studies have shown that adolescents feel ashamed going to these health centers for information or services relating to sex and contraception due the perception of unwelcoming attitude at the facility (70,71), there is evidence that delivering quality services that are tailored to adolescents needs (e.g., extension in operation hours, reduction in prices of SRH services, transforming physical design to promote privacy or confidentiality) may result in an improvement in service use, adherence to contraceptive methods, and increase the probability of seeking on-going health care (1,72).…”
Section: Discussionmentioning
confidence: 99%
“…Not different from previous studies [e.g., Maravilla et al (53)], non-pregnant adolescents in the current study were more likely to have access to pregnancy prevention information from health facilities and health workers compared to pregnant adolescents. Available literature has shown that health workers are effective in the provision of community health information to both young and old people on SRH issues to develop not only adolescent reproductive health but also a wider range of maternal and child health issues (67)(68)(69). Similarly, although studies have shown that adolescents feel ashamed going to these health centers for information or services relating to sex and contraception due the perception of unwelcoming attitude at the facility (70,71), there is evidence that delivering quality services that are tailored to adolescents needs (e.g., extension in operation hours, reduction in prices of SRH services, transforming physical design to promote privacy or confidentiality) may result in an improvement in service use, adherence to contraceptive methods, and increase the probability of seeking on-going health care (1,72).…”
Section: Discussionmentioning
confidence: 99%
“…The sociocultural environment was another critical factor for optimizing CHW functionality. In Cambodia, kinship, social hierarchical structures, religion, patron-client relations and collectivism were shown to impact the ability of CHWs to form relationships and in uence decision-making for service utilization [45]. The CHW system in Cambodia fosters a strong identity with a structured induction training and support led by local government bodies that includes basic skills, such as communication and behavior change technique [45].…”
Section: Discussionmentioning
confidence: 99%
“…The sociocultural environment was another critical factor for optimizing CHW functionality. In Cambodia, kinship, social hierarchical structures, religion, patron-client relations and collectivism were shown to impact the ability of CHWs to form relationships and influence decision-making for service utilization [40]. The CHW system in Cambodia fosters a strong identity with a structured induction training and support led by local government bodies that includes basic skills, such as communication and behavior change technique [40].…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, kinship, social hierarchical structures, religion, patron-client relations and collectivism were shown to impact the ability of CHWs to form relationships and influence decision-making for service utilization [40]. The CHW system in Cambodia fosters a strong identity with a structured induction training and support led by local government bodies that includes basic skills, such as communication and behavior change technique [40]. Furthermore, literature on the impact of CHW use of support tools demonstrates that having culturally appropriate tools, such as narratives available through videos and storybooks, can be an important, cost effective aid to CHWs, as illustrated in a study from Pakistan, where such tools facilitated dialogue between men and women to create greater awareness of maternal care [41,42].…”
Section: Discussionmentioning
confidence: 99%